A measurement of muon neutrino charged-current interactions with a charged pion in the final state using the NOνA near detector - Rojas, Paul Nelson, author; Buchanan, Norm, advisor; Lee, Siu Au, committee member; Harton, John, committee member; Kokoszka, Piotr, committee member (Colorado State University. Libraries, 2023)
The NOνA experiment is a long-baseline neutrino experiment hosted by Fermilab. The intense NuMI neutrino beam, combined with NOνA Near Detector, provides the opportunity to study neutrino interactions at an unprecedented level. The goal of this analysis is to measure the rate of muon-neutrino charged-current interactions in the NOνA near detector resulting in the production of one muon and at least one charged pion. This thesis will present the result of the double differential cross section measurement of this process in muon kinematics of energy and angle. Excesses in the extracted signal (greater than 25%), relative to the simulation, were found at large scattering angles. These excesses were greater than the estimated uncertainties (∼15%).